2008
DOI: 10.4314/bcse.v22i3.61222
|View full text |Cite
|
Sign up to set email alerts
|

<b>Electrochemical synthesis and spectroscopic characterization of poly(N-phenylpyrrole) coatings in an organic medium on iron and platinum electrodes</b>

Abstract: The electrochemical synthesis of poly(N-phenylpyrrole) film was achieved on pretreated iron and platinum electrodes in acetonitrile solutions containing 0.1 M N-phenylpyrrole as the monomer and 0.1 M tetrabutylammonium trifluoromethane sulfonate (Bu4NCF3SO3) as the supporting-salt. The results showed that a surface treatment by 10 % aqueous nitric acid inhibits iron dissolution without preventing the N-phenylpyrrole oxidation. Very strongly adherent films were obtained at constant-potential, constant-current a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…[10][11][12][13][14] We also compared, whenever it is possible, the IR spectral data of the p-substituted N-phenylpyrroles with those that we previously reported for unsubstituted NPPY, the parent compound. 6,7 For all compounds under study, the bands observed within 3150-3100 cm -1 and those within 3000-3080 cm -1 can be assigned to the υ=C-H stretching vibrations (harmonic) of the pyrrole and phenyl rings, respectively, in agreement with the attribution of bands appearing in the same spectral region for NPPY (Tables 2 and 3). In the case of 1, in addition to these bands, a wide band, located at 3426 cm -1 , was attributed to the υO-H stretching vibration, which confirmed the presence of a hydroxyl group in the phenyl ring, and therefore the formation of the title compound.…”
Section: Spectroscopic Characterization (A) Ft-ir Spectral Studysupporting
confidence: 75%
See 2 more Smart Citations
“…[10][11][12][13][14] We also compared, whenever it is possible, the IR spectral data of the p-substituted N-phenylpyrroles with those that we previously reported for unsubstituted NPPY, the parent compound. 6,7 For all compounds under study, the bands observed within 3150-3100 cm -1 and those within 3000-3080 cm -1 can be assigned to the υ=C-H stretching vibrations (harmonic) of the pyrrole and phenyl rings, respectively, in agreement with the attribution of bands appearing in the same spectral region for NPPY (Tables 2 and 3). In the case of 1, in addition to these bands, a wide band, located at 3426 cm -1 , was attributed to the υO-H stretching vibration, which confirmed the presence of a hydroxyl group in the phenyl ring, and therefore the formation of the title compound.…”
Section: Spectroscopic Characterization (A) Ft-ir Spectral Studysupporting
confidence: 75%
“…For this reason, a number of publications have been devoted to a study of the effect of the phenyl group on the properties of the corresponding polymer [poly(NPPY)]. [4][5][6][7] For instance, Mangeney et al 4 have investigated the role of a conjugated link in poly(NPPY) between the polypyrrole backbone and the phenyl group. These authors showed that it was possible to obtain polymers with conjugated grafted groups, leading to a new class of materials in which the π-electron density of the active centre might be adjusted without synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, the authors studied the impact of the electrosynthesis environment and the electrocatalytic effect of pyrrole which has a lower oxidation potential on the Nphenylpyrrole (N-PhPy) [24][25][26][27][28] electropolymerization process. So, it turned out that the presence of small amounts of pyrrole and the optimization of the environment could lead to an improvement of the electrosynthesized poly(N-phenylpyrrole) physicochemical properties 26,27 . We showed that the use of micellar media for the electropolymerization of the N-phenylpyrrole Asian Journal of Chemistry; Vol.…”
mentioning
confidence: 99%
“…26, No. 18 (2014), [5973][5974][5975][5976][5977][5978][5979][5980] could bring many advantages such as the decrease of the oxidation potential and the increase of the polymer solubility 27 . Nevertheless, we also revealed in these works some blockings related to the insolubility of poly(N-phenylpyrrole) films obtained in organic medium 26 and to problems of films overoxidation and degradation due to the use of perchloric acid in aqueous micellar medium 16 .…”
mentioning
confidence: 99%